The safe lowest effective power of subthreshold micropulse laser treatment in Chinese patients with acute or chronic central serous chorioretinopathy - Xie, Ting; Li, Wangting; Wang, Linli; Ning, Jiafeng; Li, Zhi; Chen, Yulei; Lin, Xifeng; Du, Shaolin; Chen, Qingshan (Frontiers in Medicine, 2024)
Purpose: To assess the safe, lowest effective laser power of subthreshold micropulse laser (SML) for treating acute and chronic central serous chorioretinopathy (CSC) in Chinese patients.Methods: Patients were distinguished with acute or chronic CSC based on focal or diffuse retinal pigment epithelium (RPE) leakage on fundus fluorescein angiography (FFA), with or without widespread RPE decompensation. Patients were categorized into five groups and treated with 577 nm yellow SML according to 50% titration power. The change of best-corrected visual acuity (BCVA) and central macular thickness (CMT) were set as primary outcomes. A linear regression model assessed the correlation between different factors and outcome indicators. Result: A total of 103 patients with 127 eyes (61 with acute CSC and 66with chronic CSC) were enrolled. The baseline characteristics were balanced between the five groups (all P > 0.05). The decrease of CMT and the improvement of BCVA were related to the CMT at baseline (all P < 0.05). We found that the lowest effective laser power for acute CSC was 425mw (-225.50 µm vs.